Separation of meteor streams from the sporadic background - Jopek, Tadeusz (Kluwer Academic Publishers, 1995)
A cluster analysis procedure has been used to estimate the fraction of the sporadic interlopers (sporadis bias) identified as stream members among the observed meteor orbits. Using the artificial meteor orbits with the same distribution as the observed one, the sporadic bias is estimated for the given threshold value of the orbital similarityD c. It has been shown that in case of the radio meteor catalogues theD c values given by the formula proposed in Southworth and Hawkins (1963)and in Lindblad (1971) correspond to the sporadic bias of 8 21%. For the five radio meteor catalogues the values ofD c corresponding to the fixed bias equal to 10% and 15% are given.
Keywords: Meteors, D-criterion, orbital similarity, threshold level